Organization of Financial Reporting in Accordance with Requirements of the IFRS Taxonomy - V. Ð¡hebanova, N.; I. Yefimenko, T.; M. Orlova, V.; N. Korolova, N. (International Journal of Engineering and Technology, 2018)
The authors of the article exposed the methodical questions of introduction, new for the registration process of Ukraine of the phenomenon. It is taxonomy of the financial reporting (Ð¢FR). At the same time continued consideration of questions of the use of the financial reporting for the acceptance of administrative decisions. Essence of Ð¢FR is exposed in the context of classification and systematization of ingredients of the financial reporting. It in itself informative system and connections between the constituents of such system. Authors suggested to attribute Ð¢FR to the mathematical determined models. The construction of such modelsÂ requires the clear plan of actions in three steps: a mathematical model - an algorithm of calculation - computer program. The purpose of researches: of one timesÂ to prove that introducing in economic science of exact knowledge, enables to limit the intuitional acceptance of administrative decisions and extend the limits of application of rational methods. It will be realized on condition of the use of different methods, methods and approaches - from nonlinear, stochastic models to the modernÂ programming languages . Â Â